Efeito da composição do substrato e da presença da vegetação no comportamento térmico e hidrológico de telhados verdes - Pimentel, Fabiana Campos (2022)
The substrate and vegetation are extremely important components in green roofs. The substrate is the mean for the development of vegetation, which works together to obtain the thermal and hydrological benefits and can be enhanced in order to improve these benefits. The use of additives in green roof’s substrate, including environmental liabilities, is an interesting opportunity compared to commercial options. In this study, five substrate compositions were evaluated, three formulated with Carbonized Rice Husk (CRH) in different proportions, a commercial substrate and a substrate made from local soil. The substrates were evaluated on modular green roofs from the point of thermal and hydrological benefits, and vegetal development. The effect of the presence of vegetation on the thermal and hydrological behavior of green roofs was also evaluated from the comparative analysis of vegetated and non-vegetated modules, with the same 5 substrates. The results showed that all substrate compositions were able to reduce and delay the occurrence of maximum and minimum temperature, especially the commercial substrate during the summer. The addition of 40% of CRH in the substrate provided the greatest reduction of maximum temperatures inside the green roof modules, compared to the other substrates that used this environmental liability. On the other hand, no significant differences in the retention of precipitated volumes were observed between the evaluated substrates. The vegetation cover had great percentage variability throughout the monitoring period, with higher percentages in the months od September and October, the substrate made from local soil had the lowest percentages of cover, indicating that this substrate does not favor plant development. The presence of vegetation had a significant influence on the thermal behavior of the evaluated modules, with emphasis on the modules with commercial substrate with 10% CRH, which presented the greatest differences in maximum temperature. However, hydrologically, no significant differences were observed between the moisture content of the substrate in the vegetated and non-vegetated modules for almost all the substrates – the substrate with 40% of CRH and the commercial one showed a significant difference during winter and spring, respectively. The presence of vegetation in the modules was not determinant for the retention of precipitation, although a slight superiority of water retention was observed in the non-vegetated substrates, due to the greater exposure of the substrate to meteorological variables and loss by evaporation. A strong correlation was observed between the temperatures of the substrates and the meteorological variables, especially with the air temperature. This variable, together with the total daily radiation, also strongly correlated with the temperature difference observed between the vegetated and non-vegetated duplicates of the evaluated substrates.